2020
DOI: 10.1259/bjr.20190147
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiation and granulocyte-colony or granulocyte macrophage-colony stimulating factors (G-CSF or GM-CSF): time to think out of the box?

Abstract: Concerns have been raised about potential toxic interactions when colony-stimulating factors (CSFs) and chemoradiation are concurrently performed. In 2006, the ASCO guidelines advised against their concomitant use. Nevertheless, with the development of modern radiotherapy techniques and supportive care, the therapeutic index of combined chemotherapy, radiotherapy, and CSFs is worth reassessing. Recent clinical trials testing chemoradiation in lung cancer let investigators free to decide the use of concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…In view of observation GM-CSF is overexpressed in tumor cells after radiotherapy and induced tumor migration ( Vilalta et al, 2014 ; Vilalta et al, 2018 ). GM-CSF combined with chemoradiation could trigger abscopal effect ( Benna et al, 2020 ). Highly expressed granulocyte colony-stimulating factor (G-CSF) and granulocyte colony-stimulating factor receptor (G-CSFR) leads to poor survival in gastric cancer ( Fan et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In view of observation GM-CSF is overexpressed in tumor cells after radiotherapy and induced tumor migration ( Vilalta et al, 2014 ; Vilalta et al, 2018 ). GM-CSF combined with chemoradiation could trigger abscopal effect ( Benna et al, 2020 ). Highly expressed granulocyte colony-stimulating factor (G-CSF) and granulocyte colony-stimulating factor receptor (G-CSFR) leads to poor survival in gastric cancer ( Fan et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of chemotherapy, therapeutic use of CSFs may be considered in patients receiving radiation therapy alone if prolonged delays secondary to neutropenia are expected. However, though there were concerns regarding the safety and efficacy of combination treatment of G-CSF and CCRT, Benna et al also pointed out that no abnormal infield event was reported in patients received CSFs-chemoradiation so far (52). G-CSF could be a novel therapeutic target to mitigate the harmful effect of radiotherapy including neutropenia for the treatment of NSCLC (53).…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow depression is the most important limiting factor for using these agents in cancer treatment. Being a chemical injury to the bone marrow, cyclophosphamide is associated with de novo synthesis and release of various PGs, which could have a further adverse effect on hemopoiesis colony stimulating factors synthesized in situ by T-lymphocytes and macrophages which is also essential for proliferation and maturation of granulocytes and non granulocytes (22).…”
Section: Discussionmentioning
confidence: 99%